23. CHARACTERISTICS OF MEDICAL TREATMENT OUTCOMES IN CHILDREN WITH CONGENITAL HEART DEFECTS WITHOUT SURGICAL INTERVENTION AT CHILDREN'S HOSPITAL 2 FROM 2018 TO 2023 (Vietnam Journal of Community Medicine, 2025)
Objectives: Congenital heart defects (CHDs) are among the most common congenital anomalies and one of the leading causes of mortality in infants and children. However, due to various reasons, surgical intervention is often challenging in pediatric patients. Identifying epidemiological, clinical, paraclinical characteristics, comorbidities, and outcomes of medical treatment is essential to improve patient management.Methods: A retrospective cross-sectional study was conducted on patients with congenital heart disease who had not undergone surgical intervention, treated at Children's Hospital 2 in Ho Chi Minh City from January 2018 to December 2023.Results: Among 428 patients, the median age was 8.0 months (range: 3.0–26.1 months), and the median weight was 5.5 kg (range: 3.1–33.0 kg). Thirteen patients (3.0%) were diagnosed prenatally. A total of 81 patients (18.9%) were admitted in emergency condition. Associated congenital anomalies were present in 37 patients (8.6%), with Down syndrome being the most common (13 patients, 3.0%). The most common CHDs were ventricular septal defect (26.1%), patent ductus arteriosus (18.7%), and tetralogy of Fallot (13.3%). Medical treatment was administered to 247 patients (57.7%), with diuretics used in 59.6% of cases, ACE inhibitors in 18.2%, propranolol in 6.3%, and vasopressor agents in 16 patients (3.7%). The mortality rate was 5.6%, mainly due to severe infections.Conclusion: Medical management plays a crucial role in patients with congenital heart disease who are not indicated for surgical intervention.